2020
DOI: 10.3389/fonc.2020.543591
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits the Progression of Oral Squamous Cell Carcinoma via Inducing miR-25-5p Expression by Directly Targeting NEDD9

Abstract: Melatonin exerts anti-cancer roles in various types of cancers. However, to the best of our knowledge, its role in oral squamous cell carcinoma (OSCC) is unknown. The present study aimed to investigate the role of melatonin and its underlying mechanism in OSCC. MTT, colony formation, wound healing, and transwell invasion assays proved that melatonin played anti-tumor effects in OSCC cells by inhibiting cell viability, proliferation, migration, and invasion in a concentration-dependent manner. The RT-qPCR analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…MiR ‐ 25 ‐ 5p directly targeting NEDD9 was found in oral squamous cell carcinoma and colorectal cancer. 38 , 39 Moreover, NEDD9 expression regulated by miR ‐ 145 was revealed in lung cancer, pancreatic cancer, renal cell carcinoma, prostate cancer and glioblastoma. 40 , 41 , 42 , 43 , 44 Additionally, NEDD9 expression negatively associated with miR ‐ 125a / b was shown in pancreatic cancer, lung adenocarcinoma and melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…MiR ‐ 25 ‐ 5p directly targeting NEDD9 was found in oral squamous cell carcinoma and colorectal cancer. 38 , 39 Moreover, NEDD9 expression regulated by miR ‐ 145 was revealed in lung cancer, pancreatic cancer, renal cell carcinoma, prostate cancer and glioblastoma. 40 , 41 , 42 , 43 , 44 Additionally, NEDD9 expression negatively associated with miR ‐ 125a / b was shown in pancreatic cancer, lung adenocarcinoma and melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The melatonin is further metabolized into 6-hydroxymelatonin (6OH-MEL) by human cytochrome P450 family [ 4 ]. Evidence shows that various biological properties of melatonin, such as the circadian clock [ 5 , 6 , 7 ], sleep regulation [ 8 , 9 ], anti-inflammatory properties [ 10 , 11 , 12 ], immune modulation [ 13 , 14 , 15 ], and anti-cancer activities [ 16 , 17 , 18 ], have been well revealed. Nevertheless, the clinical and immunological function of the cytochrome P450 family in cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of miRNAs were verified in HUVECs following transfection with si- uc003pxg.1 , as well as in PBMCs from clinical samples by RT-qPCR. miR-25-5p , which is associated with cell proliferation and migration, was selected for further analysis according to previous studies ( 29 , 30 ). The results demonstrated that the expression levels of miR-25-5p were significantly upregulated following uc003pxg.1 knockdown compared with those in the control cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%